The Influence of Foreign Exchange Rate Fluctuations on the Financial Performance of Commercial Banks Listed At the Nairobi Securities Exchange - C. Lagat, Carolyn; M. Nyandema, Daniel (British Journal of Marketing Studies, 2016)
A foreign exchange rate is the price at which one currency may be converted into another. An exchange rate is an important aspect in a nation’s international trade, balance of payments and overall economic performance. This paper is based on a study that sought to understand the relationship and effects of foreign exchange liberalization on financial performance of commercial banks listed in Kenya’s Nairobi Securities Exchange. The study used a time series correlation research design with the target population being all commercial banks that are listed in the Nairobi Securities Exchange between 2006 and 2013. Data was sourced from the Central Bank of Kenya and published yearly accounts of listed banks. The study used multivariate Linear Regressions to establish the relationship between foreign exchange rate fluctuations, inflation rates, interest rates and bank performance indicators. Pearson product moment correlation (r) was applied to establish the relationship between the variables. The study found that there existed a strong positive relationship between foreign exchange rates and financial performance indicators. The positive relationship between exchange rate and financial performance may reflect how fluctuating and volatile exchange rate may have contributed to the growth of profitability of banks. The study recommends that the Government should put up more measures to increase the country’s exports.